THE PROFILE OF URINE CULTURE IN PEDIATRIC PATIENTS WITH UPPER URINARY TRACT DILATATION AT DR. SOETOMO GENERAL HOSPITAL FROM 2020-2023. - Aji, Iwan Purnomo; Renaldo, Johan; Vermasari, Naritha (Indonesian Journal of Urology, 2026)
Objective: To describe the bacteriologic profile and antimicrobial-susceptibility patterns of urine cultures from pediatric UUTD patients treated at Dr Soetomo General Hospital, Indonesia, between 2020 and 2023. Material & Methods: This retrospective descriptive study reviewed medical records of 154 inpatients aged 0–17 years with confirmed UUTD. Demographic data, cultured species, and antibiotic susceptibilities were extracted and reported as frequencies. Results: From 154 bacterial isolates, Gram-negative bacteria dominated (78.6%) compared to Gram-positive (21.4%). The most frequent species were Escherichia coli (31.8%), Pseudomonas aeruginosa (16.9%), and Klebsiella pneumoniae (12.3%). Antibiotics with the highest sensitivity against major uropathogens were amikacin (83.7%), piperacillin-tazobactam (77.6%), and meropenem (81.6%). In contrast, gentamicin and nitrofurantoin demonstrated lower sensitivities, 61.2% and 71.4%, respectively. Severe hydronephrosis occurred in 52.6% of cases and was associated with more resistant bacterial isolates. Conclusion: Urinary tract infections in pediatric UUTD patients at Dr. Soetomo General Hospital are predominantly caused by Escherichia coli, with the highest antibiotic sensitivities observed for amikacin, meropenem, and piperacillin-tazobactam. Gentamicin and nitrofurantoin should be administered based on culture results, especially for uncomplicated cystitis. Regular antibiotic resistance surveillance is essential to ensure effective empirical treatment. Keywords: Urine Culture, hydronephrosis, pediatrics, antibiotic, Escherichia coli.